EFEKTIVITAS PENGGUNAAN MEDIA PEMBELARAN INTERAKTIF ADOBE ANIMATE DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI KEKAYAAN BUDAYA INDONESIA DI SEKOLAH DASAR - Roka Ismail, Putri; Naimah, Jainatun; Sri Wahyuni, Syartika; Ance Lumbantobing, Panni (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This study was conducted to determine the effectiveness of Adobe Animate learning media with the application of problem-based learning models on the material of Indonesian cultural wealth for students of Elementary School 060883 Medan. The background of this study focuses on the low learning outcomes of students about the material of Indonesian cultural wealth in grade four. As well as teachers do not apply interactive learning media and the learning models used by teachers are more monotonous in lecture and conventional learning models. Therefore, this study aims to see the effectiveness of using interactive learning media using the problem-based learning model. The design of this study used a quasi-experiment with a pre-test and post-test. Data collection used observation, documentation, and performance tests. The data analyzed were quantitative. The results of the experimental class showed an effectiveness score of 77.04% and the control class got a percentage of 70.64%. The effectiveness value of using interactive learning media is higher than power point media 6.4%. It can be concluded that Adobe Animate interactive learning media is effective in improving student learning outcomes.